Microporous ZIF-8 nanocoating as a sensitive interface for SPR detection of antimony (III) - Anuar, Muhammad Fahmi; Fen, Yap Wing; Chyi, Josephine Liew Ying; Abdullah, Huda; Taufiq, Ahmad; Hidayat, Nurul; Tee, Tan Sin; Mahdi, Mohd Adzir (Springer, 2026)
ZIF-8 was successfully synthesised with a rhombic dodecahedral morphology, an average particle size of 262.60 ± 44.21 nm, a predominantly microporous framework, and a high surface area of 991.81 m2/g. These structural features provide abundant adsorption sites, making ZIF-8 a suitable candidate for metal ion sensing. Integrated onto a gold SPR platform, the Au/ZIF-8 sensing layer exhibited clear resonance angle shifts toward higher angles in response to increasing Sb3⁺ concentrations. The sensor achieved a strong linear response (R2 = 0.95), a sensitivity of 0.057°ppm−1, and a binding affinity constant of 1.202 ppm−1, demonstrating efficient interaction between ZIF-8 and Sb3+ ions. Overall, the physical, chemical, and optical properties of ZIF-8, together with its good reproducibility, make it a strong candidate for SPR-based antimony detection.